2010
DOI: 10.2807/ese.15.02.19463-en
|View full text |Cite
|
Sign up to set email alerts
|

Severe hospitalised 2009 pandemic influenza A(H1N1) cases in France, 1 July-15 November 2009

Abstract: From 1 July 2009 to 15 November 2009, 244 patients with 2009 pandemic influenza A(H1N1) were admitted to intensive care unit (ICU) and were compared with 514 cases hospitalised in medical wards in France until 2 November 2009. Detailed case-based epidemiological information and outcomes were gathered for all hospitalised cases. Infants and pregnant women are overrepresented among cases admitted to ICU with seven per cent for both groups respectively, and twenty per cent of ICU cases did not belong to a risk gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
70
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 0 publications
9
70
0
8
Order By: Relevance
“…The incidence is usually shown in people 65 y or more. The global incidence according to our data (24.7/100,000) is similar to published rates in the Southern hemisphere 10 but lower than the rate publishedin Slovenia. 15 Patients with underlying chronic conditions are known to be at higher risk of hospitalization due to seasonal or pandemic influenza.…”
Section: Resultssupporting
confidence: 84%
“…The incidence is usually shown in people 65 y or more. The global incidence according to our data (24.7/100,000) is similar to published rates in the Southern hemisphere 10 but lower than the rate publishedin Slovenia. 15 Patients with underlying chronic conditions are known to be at higher risk of hospitalization due to seasonal or pandemic influenza.…”
Section: Resultssupporting
confidence: 84%
“…23 Multivariate analyses in several studies confirmed that the presence of concomitant diseases strictly related to age and probably not independent of it might represent a greater risk factor for ICU admission and death. [14][15][16] Forty-two percent of the subjects in our sample who were hospitalized had at least one comorbidity, with the most common conditions being asthma (19 cases, 17%) and COPD (10 cases, 9%), whereas the remaining subjects had no comorbidities. This finding is in agreement with worldwide clinical data on 2009 H1N1 virus infection, which show that 25-50% of 2009 H1N1 patients who were hospitalized or died had no underlying comorbidities.…”
Section: Discussionmentioning
confidence: 96%
“…Our data are in accordance with previous studies showing that younger adults are more often hospitalized. [14][15][16] This could probably be attributed to the fact that older people are partially protected by the presence of pre-existing antibodies from natural exposure to the A (H1N1) strains that circulated in the year following 1918 or to vaccine- induced cross-reactivity. [17][18][19] Although several studies have shown that current and past pandemics affected mainly younger adults, 20,21 with patients younger than 50 y having a higher risk of death, 22 in a recent meta-analysis, a significant increase in the risk of hospitalization and death was found in elderly compared with non-elderly subjects, but this risk was associated with the existence of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Так, в 1957 г. при пандемии гриппа А/Н2N2/ 50% умерших женщин дето-родного возраста были беременными, что составило до 10% всех смертельных случаев от гриппа [1,2]. При по-следней пандемии 2009-2010 гг., вызванной гриппом А/ H1N1/v, летальность среди беременных составила от 2,7% во Франции до 6,9% в Великобритании [3][4][5]. В Англии за весь пандемический период летальность среди беремен-ных составила 90:100 000 клинических случаев [6].…”
unclassified
“…Грипп у бе-ременных может привести в 7% случаев к антенатальной гибели плода; в 5% -к младенческой смертности; каж-дый семнадцатый ребенок имеет риск развития врожден-ных патологий; в 57% случаев новорожденные нуждаются в наблюдении в условиях палаты интенсивной терапии [5,8,9]. Перинатальная смертность регистрируется в 5,6 раза чаще среди младенцев, рожденных женщинами, которые переболели гриппом во время беременности [6].…”
unclassified